PERLINDUNGAN HUKUM TERHADAP KORBAN PEMERKOSAAN DALAM SISTEM PERADILAN PIDANA - Lembah, Andi Muhammad Fattahudin (INSANI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The problems are What is the legal protection for the crime of rape in criminal justice? and efforts can be made to provide legal protection to victims of criminal acts of rape? This research uses normative juridical methods. Author’s conclusion: Legal protection against the crime of rape in criminal justice. Rape victims need to receive protection because victims experience very complex impacts. The impact felt by the victim is double suffering which includes physical, psychological and social suffering. The position and role of the rape victim as a witness in the trial also adds to the victim’s suffering. Rape victims experience suffering before the trial, during the trial and after the trial, therefore rape victims need protection so that the victim feels safe from all forms of threats and to guarantee the victim in her recovery efforts. The form of protection that can be provided to rape victims is the protection provided by Law Number 13 of 2006 concerning Protection of Witnesses and Victims in conjunction with Government Regulation Number 44 of 2008 concerning the provision of Compensation, Restitution and Assistance to Witnesses and Victims through LPSK (Protection Agency Witnesses and Victims). Abstrak Perlindungan hukum terhadap tindak pidana perkosaan dalam peradilan pidana, Korban perkosaan perlu mendapat perlindungan karena korban mengalami dampak yang sangat kompleks. Dampak yang dirasakan korban adalah penderitaan ganda yang meliputi penderitaan fisik, psikis, dan sosial. Kedudukan dan peran korban perkosaan sebagai saksi di dalam persidangan turut menambah penderitaan korban. Penderitaan korban perkosaan dialami korban pada saat sebelum persidangan, selama persidangan dan sesudah persidangan oleh karenanya korban perkosaan memerlukan perlindungan agar korban merasa aman dari segala bentuk ancaman dan untuk menjamin korban dalam usaha pemulihannya. Bentuk upaya perlindungan yang dapat diberikan kepada korban perkosaan adalah perlindungan yang diberikan oleh Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban jo Peraturan Pemerintah Nomor 44 Tahun 2008 tentang pemberian Kompensasi, Restitusi, serta Bantuan Kepada Saksi dan Korban melalui LPSK (Lembaga Perlindungan Saksi dan Korban).